2001
DOI: 10.1046/j.1365-2540.2001.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation in a southern beech subjected to introgressive hybridization

Abstract: Diversity and dierentiation among 11 Argentine populations of the South American southern beech, Nothofagus nervosa (Phil.) Dimitri & Milano, were studied using eight isozyme gene markers. Genetic diversity, observed heterozygosity, mean number of alleles per locus, Gregorius' genetic distance, amount of genetic dierentiation and mean level of dierentiation among populations were estimated. Introgression of N. obliqua into the gene pool of N. nervosa was analysed using two species-speci®c isozyme gene markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
2
20
1
1
Order By: Relevance
“…In Matane, only 34% of the observed hybrid offspring had fathers with exotic compo- sity may therefore lead to a lack of suitable partners, which may in turn decrease the competition that nonconspecifi c pollen experiences from P. balsamifera pollen. Such a relationship between population size and hybridization rate has been observed repeatedly, for example in the tree genera Eucalyptus ( Field et al, 2008 ) and Nothofagus ( Marchelli and Gallo, 2001 ). An extreme form was studied by Vanden Broeck et al (2004) , who analyzed the offspring from a single isolated female of P. nigra and found that it consisted completely of hybrids.…”
Section: Resultsmentioning
confidence: 55%
“…In Matane, only 34% of the observed hybrid offspring had fathers with exotic compo- sity may therefore lead to a lack of suitable partners, which may in turn decrease the competition that nonconspecifi c pollen experiences from P. balsamifera pollen. Such a relationship between population size and hybridization rate has been observed repeatedly, for example in the tree genera Eucalyptus ( Field et al, 2008 ) and Nothofagus ( Marchelli and Gallo, 2001 ). An extreme form was studied by Vanden Broeck et al (2004) , who analyzed the offspring from a single isolated female of P. nigra and found that it consisted completely of hybrids.…”
Section: Resultsmentioning
confidence: 55%
“…Gallo et al . ; Kennington & James ; Marchelli & Gallo ). Several nonexclusive factors could account for this result.…”
Section: Discussionmentioning
confidence: 99%
“…While few natural population studies have explicitly measured relative population size, similar patterns have been observed in Nothofagus , with higher hybridization rates for isolated trees surrounded by compatible species (hybrid rate; 80%) compared to trees within dense conspecific stands (0%; Gallo et al . 1997; Marchelli & Gallo 2001). In an allozyme study of E. argutifolia , the small populations exhibited the highest hybridization rates in progeny arrays (47%; Kennington & James 1997).…”
Section: Discussionmentioning
confidence: 99%